Compendium to Radiation Physics for Medical Physicists 300 Problems and Solutions - Podgorsak, Ervin B. (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This exercise book contains 300 typical problems and exercises in modern physics and radiation physics with complete solutions, detailed equations and graphs. This textbook is linked directly with the textbook "Radiation Physics for Medical Physicists", Springer (2010) but can also be used in combination with other related textbooks. For ease of use, this textbook has exactly the same organizational layout (14 chapters, 128 sections) as the "Radiation Physics for Medical Physicists" textbook and each section is covered by at least one problem with solution given. Equations, figures and tables are cross-referenced between the two books. It is the only large compilation of textbook material and associated solved problems in medical physics, radiation physics, and biophysics.